Fancy Nancy's favorite fancy words : from accessories to zany - O'Connor, Jane.; Preiss-Glasser, Robin (New York : HarperCollinsPublishers, 2008)
Fancy Nancy helps children learn the alphabet by sharing her favorite fancy words.
School Library Journal, October 2008.
Pub Weekly, April 2008.
Booklist, August 2008.
Horn Book, April 2009.
School Library Journal.
2.9
Keywords: Clothing and dress -- Juvenile fiction; English language -- Alphabet; Vocabulary; Clothing and dress -- Fiction; Alphabet; Vocabulary -- Fiction; Alphabet books